Prediction of Environmental Toxicity of Active Chemical Constituents of Ipomoea Carnea through GUSAR Software - et al., Vishal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Stability of environment is based upon the proper ecological balance and better environmental conditions, but the stability of earth is affected by the pollution and it also endangers the life and survival of all living beings on this planet. According to a report published by Lancet Commission on Pollution and Health in October month of 2017, total number of deaths caused by all type of Pollution were found to be 9 million throughout the year which was around 15times more than total deaths occur due to War, and even sometimes brutality caused byhumans. Factors that are calculated for the measurement of Eco-toxicity includes Fathead Minnow LC50 Log10 (mmol/L), Daphnia magna LC50 -Log10 (mol/L), Tetrahymena pyriformis IGC50 -Log10 (mol/L), Bioaccumulation factor Log10 (BCF) etc. As the environmental toxicity increases day by day and affects human life, so there is a need for measuring the environmental toxicity and need to take crucial steps to control it. Ipomoea carnea a plant of natural origin and it falls under the family of Convolvulaceae. This plant can also be named as Bush Morning Glory is used for measurement of environmental toxicity.In this research study it was aimed to predict environmental toxicity caused by active chemical constituents of I. carnea..This research study was conducted through GUSAR online software. The environmental toxicity caused by active chemical constituents of I.carnea was predicted. As per the study results, the active chemical constituents of I. carneawere predicted to cause environmental toxicity.